2015
DOI: 10.1016/j.sbspro.2015.06.214
|View full text |Cite
|
Sign up to set email alerts
|

Methods and Techniques of Adaptive Web Accessibility for the Blind and Visually Impaired

Abstract: Massive volumes of information shared on the web together with linked open data initiatives and exabytes of data generated through social networks frequently disorientates and confuses web users in their everyday interaction. Additionally, web users constitute a highly heterogeneous entities with different needs and requirements. Considering this, user adaptive software systems have been developed as a new application approach to ease the interaction between users and web information with the intent to bridge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 19 publications
3
9
0
2
Order By: Relevance
“…The main obstacles were ethical issues, such as mistrust in data protection and privacy concerns; financial issues, such as costs to purchase hardware and for internet connection; cultural issues, such as age and the knowledge gap for ICT usage; and common issues, such as the assumed information overload on the internet. These findings can be confirmed by the literature [ 29 - 31 ]. The study revealed frustration by users, which can result from searching for information—for example, when a Google search yields too many results.…”
Section: Discussionsupporting
confidence: 90%
“…The main obstacles were ethical issues, such as mistrust in data protection and privacy concerns; financial issues, such as costs to purchase hardware and for internet connection; cultural issues, such as age and the knowledge gap for ICT usage; and common issues, such as the assumed information overload on the internet. These findings can be confirmed by the literature [ 29 - 31 ]. The study revealed frustration by users, which can result from searching for information—for example, when a Google search yields too many results.…”
Section: Discussionsupporting
confidence: 90%
“…The main obstacles were ethical issues, such as mistrust in data protection and privacy concerns; financial issues, such as costs to purchase hardware and for internet connection; cultural issues, such as age and the knowledge gap for ICT usage; and common issues, such as the assumed information overload on the internet. These findings can be confirmed by the literature [29][30][31]. The study revealed frustration by users, which can result from searching for information-for example, when a Google search yields too many results.…”
Section: Ict Usage and Its Challengessupporting
confidence: 80%
“…Audio or video content categories refer to features related to sounds and video. Voice narrator is a non-visual techniques that supports the accessibility of the content and content navigation [36]. Voice narrator was found helpful in e-mobile devices health participants, Diabetes and You and Child Care Center [37].…”
Section: Audio/visual Contentmentioning
confidence: 99%